Mitochondrial DNA Damage Does Not Determine C. elegans Lifespan - Ng, Li Fang; Ng, Li Theng; van Breugel, Michiel; Halliwell, Barry; Gruber, Jan (Frontiers in Genetics, 2019)
The mitochondrial free radical theory of aging (mFRTA) proposes that accumulation of oxidative damage to macromolecules in mitochondria is a causative mechanism for aging. Accumulation of mitochondrial DNA (mtDNA) damage may be of particular interest in this context. While there is evidence for age-dependent accumulation of mtDNA damage, there have been only a limited number of investigations into mtDNA damage as a determinant of longevity. This lack of quantitative data regarding mtDNA damage is predominantly due to a lack of reliable assays to measure mtDNA damage. Here, we report adaptation of a quantitative real-time polymerase chain reaction (qRT-PCR) assay for the detection of sequence-specific mtDNA damage in C. elegans and apply this method to investigate the role of mtDNA damage in the aging of nematodes. We compare damage levels in old and young animals and also between wild-type animals and long-lived mutant strains or strains with modifications in ROS detoxification or production rates. We confirm an age-dependent increase in mtDNA damage levels in C. elegans but found that there is no simple relationship between mtDNA damage and lifespan. MtDNA damage levels were high in some mutants with long lifespan (and vice versa). We next investigated mtDNA damage, lifespan and healthspan effects in nematode subjected to exogenously elevated damage (UV- or γ-radiation induced). We, again, observed a complex relationship between damage and lifespan in such animals. Despite causing a significant elevation in mtDNA damage, γ-radiation did not shorten the lifespan of nematodes at any of the doses tested. When mtDNA damage levels were elevated significantly using UV-radiation, nematodes did suffer from shorter lifespan at the higher end of exposure tested. However, surprisingly, we also found hormetic lifespan and healthspan benefits in nematodes treated with intermediate doses of UV-radiation, despite the fact that mtDNA damage in these animals was also significantly elevated. Our results suggest that within a wide physiological range, the level of mtDNA damage does not control lifespan in C. elegans.